2021
DOI: 10.1042/bsr20211241
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic analyses of hepatocellular carcinoma to determine immunological characteristics and key nodes in gene-expression network

Abstract: Hepatocellular carcinoma (HCC) is a common malignant tumor worldwide, but effective immunotherapy is still limited for those affected. Therefore, there is an urgent need to explore the specific mechanisms governing tumor immunity to improve the survival rate for those diagnosed with HCC. In this study, we performed a new immune stratification of HCC samples into two subclasses (A and B) from The Cancer Genome Atlas and the International Cancer Genome Consortium databases, and comprehensive multi-omic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…1 a). Our previous studies have identified DRD1 as a key hub gene in the immune-phenotype gene expression regulatory network of HCC [ 18 ]. Therefore, we deeply explored DRD1 expression, which was remarkably decreased in HCC primary tumour tissues compared with normal tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a). Our previous studies have identified DRD1 as a key hub gene in the immune-phenotype gene expression regulatory network of HCC [ 18 ]. Therefore, we deeply explored DRD1 expression, which was remarkably decreased in HCC primary tumour tissues compared with normal tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was also established that DRD1 activation might enhance antitumour activities in pancreatic cancer [ 8 ]. Our previous study determined that DRD1 acts as a key regulatory gene in HCC immune signature identification [ 18 ]. However, the specific mechanism by which DRD1 regulates HCC proliferation and migration is still unclear.…”
Section: Introductionmentioning
confidence: 99%